Development of pulse-signaling algorithm for robotics control and communication - Prapot Airtan; Manukid Parnichkun; Afzulpurkar, Nitin V.; Naber, Helmut; The Siam Nawaloha Found1y Co., Ltd. (Bangkok : Asian Institute of Technology, 1997)
The research concerning with mobile robot is one of the most popular topics for robotics researchers. "Development of Autonomous Intelligent Mobile Robot" or DAIMR project is a project that tries to develop the mobile robot that can operate intelligent tasks autonomously. The sound-response ability is an ability of DAIMR series robots. This research is developed in order to implement this ability for the robots in DAIMR project. Pulse-Signaling Algorithm (PSA) makes the communication to mobile robots possible by simple pulse signal. Within this research, PSA protocol was designed to realize the efficient communication by pulse signaling. Hardware prototype for PSA was designed and developed. Programming is also the unnegligible task to make the developed hardware work. This research is concentrated on communication from operator to robot by pulse signaling (such as clap, electric pulse). Within PSA protocol, the structure of command is considered and designed to make the efficient communication to the robots. The PSA hardware is a receiver circuit that can detect sound signal and then changes it to pulse signal. The pulse signal is processed by PSA program on Z80 microprocessor (ET-BOARD V4.0) to generate output signals for actuate the output units. The programming language is assembly for Z80. The PSA software is concentrated on communication from operator to single robot without operand. By testing and evaluation of the efficiency of the developed PSA, we found that the PSA can actuate the 8- LED on ET-BOARD V4.0, can control the contacting of relays and also can drive motors correctly. Within this research, the developed PSA hardware is only a prototype. Therefore it needs to be tested and modified to become final and reliable tool for robotics control and communication.
Thesis (M.Eng.) - Asian Institute of Technology, 1997
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering, School of Advanced Technologies
Keywords: Robots -- Control systems